Mitigasi Risiko Pembiayaan Pada Bank Perkreditan Rakyat Syariah (BPRS) Safir Cabang Curup Kabupaten Rejang Lebong - Rahayu, Ika Gustin; Hendrianto, Hendrianto (Sekolah Tinggi Agama Islam Negeri Curup, 2018)
Increasingly better risk mitigation will help realize the objectives of the BPRS, namely to improve the economy of the lower middle class. BPRS as one of the microfinance institutions must be faced with risks, especially financing risks. The purpose of this study is to find out the risk mitigation actions carried out by BPRS SAFIR in order to minimize risks properly. This research is a field research (field research) that uses a qualitative approach withmethod descriptive analysis. Data collection used is interviews with accounting staff and secondary data from the literature related to risk in BPRS. The analysis technique used is to classify the data obtained with each category which is then analyzed. The results of this study are: There are several stages of financing procedures at BPRS SAFIR, first is the submission of a financing application, the second is submission of the file to the Account Officer; Third initial survey by the Account Officer in charge, Fourth follow-up survey with several Account Officers; The five decisions on funding by branch managers, the sixth realization decision. The financing risk faced by BPRS SAFIR is credit risk and strategic risk, these two risks are also prioritized by BPRS SAFIR because they are caused by both partners. The mitigation measures of BPRS SAFIR in reducing risk are carried out by:First, establishing certain conditions for each financing that must be met by prospective recipients of financing facilities.The two binding guarantees are fixed assets and movable assets. Third, do monitoring periodic.